Biselectivity of isoDGR peptides for fibronectin binding integrin subtypes α5β1 and αvβ6: conformational control through flanking amino acids - Bochen, Alexander; Marelli, Udaya Kiran; Otto, Elke; Pallarola, Diego; Mas-Moruno, Carlos; Di Leva, Francesco Saverio; Böhm, Heike; Spatz, Joachim P.; Novellino, Ettore; Kessler, Horst; Marinelli, Luciana (Journal of medicinal chemistry, 2013)
Integrins are the major class of cell adhesion proteins. Their interaction with different ligands of the extracellular matrix is diverse. To get more insight into these interactions, artificial ligands endowed with a well-defined activity/selectivity profile are necessary. Herein, we present a library of cyclic pentapeptides, based on our previously reported peptide motif c(-phg-isoDGR-X-), in which high activity toward fibronectin binding integrins α5β1 and αvβ6 and not on vitronectin binding integrins αvβ3 and αvβ5 has been achieved by changing the flanking amino acids. The structure of the most promising candidates has been determined using a combined approach of NMR, distance geometry, and molecular dynamics simulations, and docking studies have been further used to elucidate the peptide-integrin interactions at the molecular level. The peptides’ binding affinity has been characterized by enzyme linked immunosorbent assay experiments, and the results have been verified by cell adhesion experiments on specifically functionalized surfaces.
Gesehen am 27.11.2020